Functioning of the Clothing Networks on the Global Markets - Comparative Analysis - Malinowska-Olszowy, Monika (Comparative Economic Research. Central and Eastern Europe, 2012)
The globalisation process contributes to shaping of many diverse consequences, among others it causes the internationalization of production, new, global division of work, increase of competitiveness, it builds the branches of a globalising business. From the point of view of economy, the phenomenon of globalisation influences the deepening of a free float of commodities, services, resources, capital, work, and also information between the countries. These factors significantly contribute to many changes that are visible in the operations of the latter-day enterprises (Penc 2003, p. 152). One of the consequences of the globalisation process, which is directly connected with the functioning of companies, is the necessity of building and managing the brand. As a result it creates many possibilities to global companies from the textile-clothing sector that want to achieve a market success. However, in order to achieve it one has to fulfill many, constantly increasing, expectations of the buyers. The realisation of these challenges is possible only with the share of two crucial factors: proper competitiveness and progressive marketing strategies. In the clothing sector the partnership networks are being created between the economic subject, because such actions are aimed at minimising the risk, as well as to reducing the production and distribution costs. The most often encountered networks in the textile-clothing branch are the franchising networks. The present article concentrates on the competitiveness aspect of the global clothing networks. A comparative analysis of the action of the commercial clothing networks was made, in order to show some features of its operation and proceeding, while focusing on the specified elements of the marketing-mix strategy. The obtained results allowed to show the differences and similarities in the used marketing strategies.